CUYANIA, AN EXOTIC BLOCK TO GONDWANA: REVIEW OF A HISTORICAL SUCCESS AND THE PRESENT PROBLEMS - Ramos V.A. (My University, 2004)
A review of the early history of the Cuyania terrane and the numerous pioneering works of the past century provides the present robust framework of evidence supporting a derivation from Laurentia, travel towards Gondwana as an isolated microcontinent, and final amalgamation to the protomargin of western Gondwana in Middle to Late Ordovician times. The major remaining uncertainties and inconsistencies, such as the time of deformation and collision with Gondwana, the lack of evidence of Famatinian-derived zircons, the effects of strike-slip displacements proposed along the suture, as well as the potential sutures defined by ophiolite assemblages, are discussed. The precise boundary along the northern and southern limits is not yet well defined.
Keywords: West Gondwana; Laurentia; Cuyania; accretion; early Paleozoic; Precordillera